Estado nutricional, nivel socioeconómico y trastornos de la conducta alimentaria en estudiantes de nivel secundario de la I.E. 60168 Fernando Lores Tamshiyacu, 2023 - Alva Linares, Mackeisie Alexandra (2024)
The objective of this research was to determine the relationship between nutritional status and socioeconomic status and eating disorders in high school students at I.E. 60168 Fernando Lores – Tamshiyacu. The study was correlational, non-experimental, quantitative and cross-sectional. The methodological design was observational, descriptive in nature. It was probabilistic and stratified. The sample consisted of 149 fourth and fifth grade high school students. The eating disorder questionnaire, socioeconomic status questionnaire and nutritional evaluation form were used. It was found that 1074% were overweight, 11.41% were short, 7.38% were at high risk and 1.34% were at very high risk according to abdominal perimeter and 44.97% had optimal body fat. Different degrees of anemia were found between females and males. Most students have a low, inferior and marginal socioeconomic level. 31.54% of students were at risk of eating disorders. It was concluded that there was a significant statistical relationship between socioeconomic level and eating disorders with nutritional status, but no relationship was found between socioeconomic level and height for age.